2018
DOI: 10.1101/402735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Task-specific vision models explain task-specific areas of visual cortex

Abstract: Computational models such as deep neural networks (DNN) trained for classification are often used to explain responses of the visual cortex. However, not all the areas of the visual cortex are involved in object/scene classification. For instance, scene selective occipital place area (OPA) plays a role in mapping navigational affordances. Therefore, for explaining responses of such task-specific brain area, we investigate if a model that performs a related task can serve as a better computational model than a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…More ethologically-relevant and embodied tasks such as navigation, object manipulation and visual reasoning, may be needed to capture the full diversity of visual processing and its relation to other brain areas. Early versions of this idea are already being explored [118,119 ]. The study of insect vision has historically taken this more holistic approach and may make for useful inspiration [120].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…More ethologically-relevant and embodied tasks such as navigation, object manipulation and visual reasoning, may be needed to capture the full diversity of visual processing and its relation to other brain areas. Early versions of this idea are already being explored [118,119 ]. The study of insect vision has historically taken this more holistic approach and may make for useful inspiration [120].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Therefore we can use the predictive regions from each of the models to identify the brain regions where specific task-relevant information is localized. Independently, Dwivedi and Roig [17] has shown that representation similarity analysis (RSA) performed between task representations and brain representations can differentiate scene-selective regions of interest (ROIs) by their preferred task. For example, representations in scene-selective occipital place area (OPA) are more highly correlated with representations from a network trained to predict navigational affordances.…”
Section: Introductionmentioning
confidence: 99%